2016
DOI: 10.1103/physrevd.94.064022
|View full text |Cite
|
Sign up to set email alerts
|

Deformed matter bounce with dark energy epoch

Abstract: We extend the Loop Quantum Cosmology matter bounce scenario in order to include a dark energy era, which ends abruptly at a Rip singularity where the scale factor and the Hubble rate diverge. In the "deformed matter bounce scenario", the Universe is contracting from an initial non-causal matter dominated era until it reaches a minimal radius. After that it expands in a decelerating way, until at late times, where it expands in an accelerating way, thus the model is described by a dark energy era that follows t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 113 publications
(228 reference statements)
1
20
0
Order By: Relevance
“…Thus, a matter bounce scenario based on the matter content observed in the universe today can naturally predict scale-invariant perturbations with a slight red tilt and a small tensor-to-scalar ratio [7]. Further properties of such a matter bounce scenario with dark matter and dark energy, as well as some extensions thereof, have been studied in [8,[14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a matter bounce scenario based on the matter content observed in the universe today can naturally predict scale-invariant perturbations with a slight red tilt and a small tensor-to-scalar ratio [7]. Further properties of such a matter bounce scenario with dark matter and dark energy, as well as some extensions thereof, have been studied in [8,[14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been verified that in a sum of two exponential functions model of the scale factor, asymptotic behavior at late-time cosmic acceleration is similar to that of the model discussed above. Recently there was an paper [38] one can demonstrated that in the context of LQC, it is possible to realize a deformed matter bounce scenario, in which the deformation practically alters the late-time behavior of the model. Would be interesting to apply the proposed mechanism for the constructed in our paper models.…”
Section: Discussionmentioning
confidence: 99%
“…We dispose now of all the necessary ingredients to calculate the power spectrum of the primordial scalar gravitational perturbations. Indeed, if we substitute (35) into (20), we find that the power spectrum of the primordial curvature perturbations is expressed by the relation…”
Section: The Power Spectrum Of Scalar Gravitational Perturbationsmentioning
confidence: 99%
“…We wish to remark that recently bouncing cosmologies involving dark matter (and dark energy) have received much attention in the literature, and that distinctive and falsifiable predictions on CMB observables have been derived that will be tested in the near future [13][14][15][16][17][18][19][20] (for a recent review see also [21]). With respect to this vast literature the gist of our proposal relies on the deployment of fermionic matter fields.…”
Section: Introductionmentioning
confidence: 99%